Kesenjangan Digital dalam Dunia Pendidikan Masa Kini dan Masa Yang Akan Datang: Studi Kasus di SMP N 35 Medan - San Mikael Sinambela; Joy Novi Yanti Lumbantobing; Mima Defliyanti Saragih; Al Firman Mangunsong; Chairun Nisa; Johan Pardamean Simanjuntak; Jamaludin Jamaludin (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted to determine the digital gap in the world of education today and in the future. This research method is to use a qualitative method with an observational study approach. The result of this research show that in the school that was used at the research site, there still a digital divide where there are still many students who still have limitations in owning electronic goods due to economic limitations and the distance from home to school whis is quite far. In conclusion, the school has tried as much as possible to equalize digital use for students who do not have electronic devices to use computers provided by the school.